THE EFFECT OF PRE-TREATMENT ON THE EFFECTIVENESS OF PALMBASED POLYVINYL CHLORIDE MIXED METALS STABILIZER - Evania Silitonga, Dorotea
Polyvinyl Chloride (PVC) is one of the most widely used thermoplastic polymers in the world. This is supported by the wide application of PVC in the construction sector. However, PVC also has a disadvantage which is its low thermal stability characteristic. The thermal degradation of PVC occurs at a temperature of 100oC, meanwhile PVC mainly processed at 160 – 210oC. Thermal degradation of PVC is caused by defects in the polymer chain in the form of tertiary chlorine atoms and allylic chlorine atoms that occur due to the polymerization process that trigger dehydrochlorination in the form of hydrochloric acid. To overcome these problems, it is necessary to add additives in the form of thermal stabilizers to prevent thermal degradation. In general, the stabilizer is used to bind unstable chlorine atoms that will prevent the formation of HCl or dehydrochlorination reactions, it also neutralize the HCl that has been formed. One type of thermal stabilizer that is commonly used is a mixed metal stabilizer, especially a mixture of Ca-Zn. Mixed metal stabilizer is the safest, but its stabilizing effect is lower than other types. Therefore, process engineering is needed to increase the effectiveness of metal soaps such as pre-treatment of metal mixtures in the form of preheating. The preheating has a synergistic effect on the CaSt2 and ZnSt2 stabilizers by forming a complex. The purpose of this study is to examine the effect of pre-treatment of palm-based mixed metal stabilizer on PVC thermal stability and which pre-treatment is the most effective. The further experiment is conducted by using dehydrochlorination test. Complex compound analysis is performed by FTIR. In this research, PVC resin stabilized with pre-heated palm-based mixed metal thermal stabilizer developed at the RPIP ITB Lab will be tested for its thermal stability. Red Congo test and the dehydrochlorination test will be used in this study. Complex compound will be analyzed by FTIR. Variations of the experiment carried out were variations in pre-heating temperature and time to get the best formula. The results of this study indicate that preheating of the PVC thermal stabilizer, Ca/Zn-PFAD, showed signs of complex formation similar to Ca/Zn-St. The effect of this preheating able to significantly increase the effectiveness of the Ca/Zn-PFAD PVC thermal stabilizer. The most effective preheating temperature and time obtained from this study were 100oC and 30 minutes.